A review on the factors influencing the adoption of new mobility technologies and services: autonomous vehicle, drone, micromobility and mobility as a service. Issue 3 (4th May 2023) - Zhang, Yuerong; Kamargianni, Maria
ABSTRACT: New mobility technologies and services could address a series of transport-related problems such as pollution, congestion, unpleasant travel experiences, as well as first- and last-mile in-connectivity. Understanding the key factors influencing adoption and enablers is critical to the rollout of the new mobility technologies and services. The objective of this paper is to conduct a systematic review of the new mobility technologies and services, especially on autonomous vehicles, drones, micromobility and Mobility as a Service (MaaS). The ultimate goal is to gain a deeper insight into the factors that affect the adoption or preferences of these technologies and services and thus provide policy implications at the strategic level. The results of the review identified several (1) shared, (2) exclusive, (3) opposing and (4) mixed impacts factors that strongly influence the uptake of new mobilities. The synthesised finding will contribute to policy decisions, particularly regarding the sequencing of the launch and development priorities of new mobility technologies and services. To encourage the uptake of new mobility technologies and services, further promotion would benefit from (1) embedding a spatio-temporal perspective, (2) undertaking a careful market segmentation and (3) a careful segmentation of technology and services based on features, application contexts and purposes.